Обґрунтування сучасних моделей та систем підтримки організаційної творчості - Лісовська, Л. С.; Теребух, А. А.; Гацук, М. М.; Lisovska, L.; Terebukh, A.; Hatsuk, M. (Видавництво Львівської політехніки, 2019)
Автори виокремили та обґрунтували шість моделей розуміння креативності та творчого процесу. Використання цих сучасних та загальноприйнятих моделей дає змогу пояснити феномен “креативності” різними компонентами, стадіями або фазами. Особливої уваги автори надали вивченню та проведенню характеристики процесу організаційної творчості на прикладі модифікованої моделі Уолласа, зокрема деталізовано компоненти формування етапів та фактори впливу на різних етапах. На підставі аналізування наукових джерел автори сформували узагальнену модель творчого процесу, визначили завдання кожного етапу організаційної творчості та силу та напрям дії факторів зовнішнього середовища. У статті проведено економічне обґрунтування доцільності впровадження Системи підтримки організаційної творчості на прикладі вітчизняної організації ТОВ “Енерготехпром”. Для розробки системи управління знаннями на підприємстві були визначені основні технічні вимоги до системи, на основі розробленої схеми була визначена приблизна вартість розробки та утримання даної системи (за умови аутсорсингу). Розрахунок ефективності впровадження цього інноваційного проекту був здійснений відповідно до міжнародних стандартів та підтвердив доцільність реалізації проекту.

The authors identified and substantiated six models of understanding creativity and the creative process. Usage of these modern and generally accepted models can explain the phenomenon of “creativity” by various components, stages or phases. The authors paid particular attention to studying and conducting the characteristics of the process of organizational creativity on the example of the modified Wallace model. In particular, the components of the formation of stages and factors of influence at different stages were elaborated. Based on the analysis of scientific sources, the authors formulated a generalized model of the creative process, identified the tasks of each stage and the strength and direction of the environmental factors. This model can be used to further identify the factors of influence, both internal and external, on organizational creativity at different stages of the creative process. To facilitate the creation and development of organizational creativity, authors suggest using an intelligent system with a temporary knowledge base. Such systems not only contain the actual base, the basis of rules and the mechanism of conclusions but also directly solve issues related to the time frame. In practice, they are called creativity support systems, and they unite various types of information systems to improve creativity. Creativity support systems can be used to enhance the user’s ability to perform creative tasks (the ability that the user owns), to support users in the field of acquiring knowledge, and to provide users with a new experience of creative tasks, which gives them new abilities. There are two types of creative support systems: individual creativity support systems and group creative support systems. The authors substantiate the expediency of creating and using the complex type of systems of support for creativity called “System of support of organizational creativity”. The system of support for organizational creativity opens a new form of creative support. Unlike previous types of systems, such a system allows to increase the competitive advantages of an organization and its productivity by offering quick access to various, heterogeneous, branched out information resources, analyzing them, visualizing them and offering recommendations for creating new useful ideas. The article provides an economic justification for the feasibility of introducing a system of support for organizational creativity on the example of the domestic organization of LLC Energotekhprom. The primary technical requirements for the system were determined to develop a knowledge management system at the enterprise. Based on the developed scheme, the approximate cost of developing and maintaining this system (subject to outsourcing) was determined. The calculation of the effectiveness of the implementation of this innovation project was carried out following international standards and confirmed the feasibility of the project.
Grounds of modern models and systems of organizational creativity support
Keywords: організаційна творчість; системи підтримки творчості; моделі творчого процесу; Системи підтримки організаційної творчості; креативна підтримка; organizational creativity; systems of support of creativity; models of creative process; systems of support of organizational creativity; creative support; 331.108; 26